Impaired CD23 and CD62L expression and tissue inhibitors of metalloproteinases secretion by eosinophils in adults with atopic dermatitis. (13th July 2016) - de Oliveira Titz, T.; Orfali, R.L.; de Lollo, C.; dos Santos, V.G.; da Silva Duarte, A.J.; Sato, M.N.; Aoki, V.
Abstract: Background: Eosinophils are multifunctional, polymorphonuclear leucocytes that secrete proteins within cytoplasmic granules, such as cytokines, chemokines, metalloproteinases (MMPs) and metalloproteinases tissue inhibitors (TIMPs). Although eosinophilia is a hallmark of atopic dermatitis (AD), several functional aspects of eosinophils remain unknown. Objective: We aimed to evaluate the phenotype and functional response of eosinophils under staphylococcal enterotoxin B (SEB) and Toll‐like receptor (TLR)‐2/6 (FSL‐1) stimulation in the secretion of CCL5, MMPs and TIMPs in adults with AD. Methods: Forty‐one adult patients with AD and 45 healthy controls enrolled for the study. Phenotype of eosinophils from granulocytes of peripheral blood was analysed by flow cytometry. We performed evaluation of CCL5 (cytometric bead array), MMP and TIMP (ELISA) secretion, in culture supernatants of purified eosinophils stimulated with SEB or TLR2/6 agonist (FSL‐1). Results: We found a higher frequency of LIN1 − CCR3 + eosinophils, and decreased expression of CD23 and CD62L receptors in eosinophils of AD patients. There was no difference in MMP and TIMP serum levels between the evaluated groups. However, we detected decreased basal levels of TIMP‐1, TIMP‐2 and CCL5 in culture supernatants from purified, unstimulated eosinophils from AD patients. Conclusion: In adults with AD, phenotypical features of eosinophils reveal decreased expression of early activation and L‐selectin receptors. Regarding the functional profile of purified eosinophils related to tissue remodelling in atopic dermatitis, innate immune stimulation (TLR2/6 agonist and SEB) did not affect the ratio of MMP/TIMPs secretion in AD. Our findings reinforce the potential breakdown in tissue remodelling process mediated by eosinophils in AD.